Effect of Peat on Physicomechanical Properties of Cemented Brick - Syed Mofachirul Islam; Roslan Hashim; A. B. M. Saiful Islam; Ryan Kurnia (The Scientific World Journal)
The popularity of low cost, lightweight, and environmentally affable masonry unit in building industry carries the need to investigate more flexible and adaptable brick component as well as to retain the requirements confirmed in building standards. In this study, potential use of local materials used as lightweight building materials in solving the economic problems of housing has been investigated. Experimental studies on peat added bricks have been carried out. It demonstrates the physicomechanical properties of bricks and investigates the influence of peat, sand, and cement solid bricks to the role of various types of constructional applications. The achieved compressive strength, spitting strength, flexural strength, unit weight, and ultrasonic pulse velocity are significantly reduced and the water absorption is increased with percentage wise replacement of peat as aggregate in the samples. The maximum 20% of (% mass) peat content meets the requirements of relevant well-known international standards. The experimental values illustrate that, the 44% volumetric replacement with peat did not exhibit any sudden brittle fracture even beyond the ultimate loads and a comparatively smooth surface is found. The application of peat as efficient brick substance shows a potential to be used for wall and a viable solution in the economic buildings design.